Wearable temperature sensor for human body temperature detection - Kuzubasoglu, Burcu Arman; Sayar, Ersin; Cochrane, Cedric; Koncar, Vladan; Bahadir, Senem Kursun (Journal of materials science. Materials in electronics, 2021)
This paper presents the production and the characterization of the multi-walled carbon nanotube (MWCNT) printed flexible temperature sensors for high-precision reading in temperature sensing applications. The temperature sensor was fabricated using the inkjet printing method by depositing carbon nanotube (CNT) ink on soft taffeta fabric. An aqueous CNT-based conductive ink was formulated for the inkjet printing process. A translucent polyurethane (PU) welding tape was used as an encapsulation layer on the surface of the sensors to protect sensors from various environmental effects during usage and testing. The fabricated sensors function as thermistors, as the conductivity increases with temperature linearly. The performances of differently patterned three temperature sensors were compared. The highest obtained temperature coefficient of resistance (TCR) and the thermal index are −1.04%/°C and 1135 K, respectively. The fabricated sensors possess a high-temperature sensitivity between room temperature and 50 °C and perform better than the typical commercial platinum temperature sensors and most of the recently reported CNT-based temperature sensors in the literature.